INCIDENCE OF PSEUDOHERMAPHRODITISM IN THE SPINY LOBSTER PANULIRUS HOMARUS (LINNAEUS) - Radhakrishnan, M V; Vijayakumaran, M; Hameed, K Shahul (Indian Journal of Fisheries, 2011)
Specimens of the spiny lobster, Panulirus homarus ranging in size from 22.3 - 97.5 mm carapace length (67 - 245 mm total length) with well developed male genital system, but with biramous pleojxxls (as in females) were recorded in 1987,1988 and 1989 from trammel net catches off Kovalam, near Madras. The probable factors responsible for this sexual abnormality have been discussed.